Detection of Black Hole Attack in DTN with Authentication (International Journal of Engineering and Computer Science, 2015)
DTN such as sensor networks with schedule occurring at irregular intervals and the packets transferring will be referred to as store–carry-forward technique. Here the routing is decided with characterized by opportunity. These nodes will be acts like malicious node. Here the malicious behaviour can be occurred due to the attacker/hacker who leads to lose of data and increases remission delay, to overcome this problem we are using the SERVICE PROVIDER term which provides the services to the senders and the receivers with confidentially. By using the Vehicular Algorithm, we can detect Black Hole Attack and we can improve the security and the authentication to our data and it chooses the shortest path to transfer the data from sender to receiver, if the chosen path can have the malicious node then immediately router skip to another path which is nearer to it.